Analysis and Design of Student Financial Information System at The Institut Bisnis dan Informatika Stikom Surabaya - Andari, Yuli Setiyo Suryo; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Finance Department of Institut Bisnis dan Informatika Stikom Surabaya, the student finance has primary responsibility to provide services to students, has implemented a information system on the service process. But still found some manual processes, to cause human error and a lot of wasted time.Based on the existing problems, then made the analysis and design of student financial information systems at the Institut Bisnis dan Informatika Stikom Surabaya described in System Flow, Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD), interface design, and the database structure to solution to replace manual processes with an integrated system.The results of this research is the analysis and design of student financial information systems that can replace the manual storage, manual calculation process, the manual checking and reporting process, can eliminate human error and speed up the process of service. The results of their designs can also be used as a document for the system development.